Pengaruh Kegiatan Menganyam Kain Flanel Terhadap Kemampuan Motorik Halus Anak di PAUD Tunas Bangsa Padang - Martika, Junia Sri; Mayar, Farida (Jurnal Caksana : Pendidikan Anak Usia Dini, 2019)
Abstract: The study aims to determine the effect of weaving activities using flannel cloth on children’s fine motor skills in Paud Tunas Bangsa Padang. Fine motor development activities found in the field tended to be coloring and drawing.  Therefore, through this weaving activity with flannel cloth, researchers wanted to see how the development of child fine motoric in the Paud Tunas Bangsa Padang. The research method used is quantitative with a Quasi Experimental from. The population is 34 students of the Paud Tunas Bangsa Padang. Namely groups A1, B1, B2. Groups B2 is made as experimental sample and B1 control sample is 10 people each. The sampling technique is used cluster sampling. And as for the data collection techniques used tests made by teachers such as statements og 4 pieces of statements and data collection in the form of statement sheets in the from of instrument lattices. The difference test results in the experimental average were 78.75 while the controls were 71.25. it can be concluded that there is a significant effect of weaving activities using flannel cloth on the fine motor skills of children at Paud Tunas Bangsa Padang.